Ministry of truth ebook Democracy, reality, and the republicans' war on the recent past. - Benen, Steve (2024)
Instant New York Times Bestseller A searing, vital investigation of the Republican Party's dangerous campaign to rewrite recent history in real time, from the Emmy Award-winning Rachel Maddow Show producer and bestselling author of The Impostors. "There is nobody who is writing in an episodic way who has more influence on the way I think about politics than Steve Benen." — Rachel Maddow For as long as historical records have existed, authoritarian regimes have tried to rewrite history to suit their purposes, using their dictatorial powers to create myths, spread propaganda, justify decisions, erase opponents, and even dispose of crimes. As the Republican Party becomes increasingly radicalized, the GOP is putting their own twist on a similarly despotic script. Indeed, the party is taking dangerous, aggressive steps to rewrite history—and not just from generations past. Unable to put a positive spin on Trump-era scandals and fiascos, GOP voices and their allies have grown determined to rewrite the stories of the last few years—from the 2020 election results and the horror of January 6th to their own legislative record—treating the recent past as an enemy to be overpowered, crushed, and conquered. The consequences for our future, in turn, are dramatic. Extraordinarily timely and undeniably important, Steve Benen's new book tells the staggering chronicle of the Republican party's unsettling attempts at historical revisionism. It reveals not only how dependent they have grown on the tactic, but also how dangerous the consequences are if we allow the party to continue. The stakes, Benen argues, couldn't be higher: the future of democracy hinges on both our accurate understanding of events and the end of alternative narratives that challenge reality.